STRATEGI PENGEMBANGAN AGROINDUSTRI BERAS SIGER DI DESA WONOKARTO KECAMATAN SEKAMPUNG KABUPATEN LAMPUNG TIMUR DAN DESA MARGOSARI KECAMATAN PAGELARAN UTARA KABUPATEN PRINGSEWU - Rizky Ramdhani Puspanegara; Raden Hanung Ismono; Eka Kasymir (Lampung University, 2020)
This research aims to analyze development strategies of siger rice agroindustry. This research uses a case study method. The samples are two different siger rice agroindustries and stakeholders on agroindustry. The method of data analysis used are descriptive analysis and SWOT analysis. The results of this research showed that, for Wonokarto village, the combination of IFE and EFE values was 1.81 and 1.51, and for Margosari Village was 0.56 and 1.38. Both combinations in the IE matrix shows that the positions are in quadran, meaning that the agroindustries are in the growth position. The best priority strategies for growing agroindustry are increasing the quality of the product and making an innovation for the product.Key words: development strategy, siger rice, SWOT analysis